Drug utilization study in patients of COPD in TB and Chest department in a tertiary care teaching hospital - Vyas, Abhishek Y.; Dumra, Gurusharan H.; Singh, A. J. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a major cause of chronic morbidity and mortality throughout the world. It is the fourth leading cause of death in the world, and further increase in its prevalence and mortality can be predicted in the coming decades. Many people die prematurely from it or its complications. Total deaths from COPD are projected to increase by more than 30% in the next 10 years unless urgent action is taken to reduce the underlying risk factors, especially tobacco use. Estimates show that in 2020 COPD will become the third leading cause of death worldwide. A wide range of drugs are prescribed for COPD but not strictly according to established guidelines. Methods: A prospective observational study of drugs prescribed in COPD was conducted in outdoor patients at TB and Chest department at Sheth L. G. General Hospital. Results: Total 90 prescriptions of COPD patient were collected and studied for drug utilization. The results revealed that the ratio of prevalence in males was higher than females, which was 73% and 27% respectively. Theophylline (93.3%) and chlorpheniramine (71.1%) were most prescribed drugs. Conclusions: According to the results, prevalence was higher in males than females and was higher in smokers than nonsmokers and most common prescribed class of drug was methylxanthine.